"What" matters more than "Why" – Neonatal behaviors initiate social responses. (13th December 2017) - Libertus, Klaus; Libertus, Melissa E.; Einspieler, Christa; Marschik, Peter B.
Abstract: Newborns are born into a social environment that dynamically responds to them. Newborn behaviors may not have explicit social intentions but will nonetheless affect the environment. Parents contingently respond to their child, enabling newborns to learn about the consequences of their behaviors and encouraging the behavior itself. Consequently, newborn behaviors may serve both biological and social-cognitive purposes during development.